2006
DOI: 10.1681/asn.2005111167
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Agonists Exacerbate Accelerated Nephrotoxic Nephritis

Abstract: Glomerulonephritis can be exacerbated by infection. This study investigated the effect of N-palmitoyl-S-(2,3-bis(palmitoyloxy)-(2R,S)-propyl)-(R)-cysteinyl-seryl-(lysyl)3-lysine (Pam 3 CysSK 4 ), a synthetic Toll-like receptor 2 (TLR2) ligand, that was given at immunization on disease severity in accelerated nephrotoxic nephritis. Stimulation of TLR by microbial constituents is known to influence the development of the adaptive immunity. It was hypothesized that the TLR2 ligand Pam 3 CysSK 4 can modulate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 42 publications
1
49
0
1
Order By: Relevance
“…We have recently demonstrated that TLR2 ligands given at the time of priming to the planted antigen can exacerbate disease in this model by modulating the nephritogenic immune response. 16 In addition to our own studies, Fu et al 17 also gave endotoxin and other TLR ligands to mice at the same time as nephrotoxic antibody. However, in this work there was no measurement of the immune response to the nephritogenic antigen sheep IgG, and so the relative roles of effects on the adaptive immune response or on innate mechanisms were not clear.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…We have recently demonstrated that TLR2 ligands given at the time of priming to the planted antigen can exacerbate disease in this model by modulating the nephritogenic immune response. 16 In addition to our own studies, Fu et al 17 also gave endotoxin and other TLR ligands to mice at the same time as nephrotoxic antibody. However, in this work there was no measurement of the immune response to the nephritogenic antigen sheep IgG, and so the relative roles of effects on the adaptive immune response or on innate mechanisms were not clear.…”
mentioning
confidence: 58%
“…16 In brief, crescents and thrombosis were scored on samples fixed in Bouin's solution and stained with PAS. For thrombosis, 50 glomeruli were each scored out of 4.…”
Section: Assessment Of Diseasementioning
confidence: 99%
See 3 more Smart Citations